Relative age effects in the selection of representative athletes of Kosovo national team in handball, football, basketball, volleyball - Post puberty age - Haxhnikaj, L.; Miftari, F. (SportMont, 2023)
Taking into account the role that the selection of athletes has in the success of clubs as well as in the sports life of young people, this research aims to highlight the impact of the Relative Age Effects (RAE) in the selection of athletes for representative teams of Kosovo in collective sports and the difference between the respective groups. The study was designed as an observational cross-sectional study. The total sample of persons in this research was n=237 (118 male and 119 female) athletes of the Kosovo National Team of team sports. The athletes were divided into 4 main groups: Q1 (January-March), Q2 (April-June), Q3 (July-September) and Q4 (October-December) with a special emphasis on the Q1 and Q4 group (for all sports the birth dates of the age post-puberty were collected). The analysis of the data clearly indicates that young athletes born in Q1 and Q2 were significantly more selected for representative teams compared to those in the other two groups. The results demonstrate a significant relative age effect on athlete selection based on gender for the Kosovo National Team. Specifically, athletes from Q1 and Q2 were favored. Based on these findings, it is strongly recommended that the respective federations, sports trainers, and relevant sports authorities take proactive measures to prevent the "discrimination" experienced by young athletes.